2022
DOI: 10.3389/fphar.2022.902016
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin synthase 2 is a positive regulator of the CSF1R-STAT3 pathway in pancreatic cancer-associated macrophage

Abstract: Background: Tumor-associated macrophages (TAMs) are one of the most abundant immune cells in the pancreatic cancer stroma and are related to the poor prognosis of pancreatic ductal adenocarcinoma (PDAC) patients. Therefore, targeting tumor-associated macrophages is a possible strategy for the treatment of pancreatic cancer.Purpose: We would like to investigate the role of sphingomyelin synthase 2 (SMS2) and the effect of the synthase 2 selective inhibitor YE2 in TAMs and the pancreatic tumor microenvironment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The transcriptome data showed that 606 genes (329 downregulated and 277 upregulated) were differentially expressed with statistical significance (Figure 4 D and Supplementary Table 3 ). Heatmap showed the significantly downregulation of TGFB1 32 , ETV1 33 , CSF1 34 , BMP7 35 , SGMS2 36 , CXCL14 37 and S100A4 38 which have been reported to enhance protumor macrophage polarization via various pathways. (Figure 4 E).…”
Section: Resultsmentioning
confidence: 99%
“…The transcriptome data showed that 606 genes (329 downregulated and 277 upregulated) were differentially expressed with statistical significance (Figure 4 D and Supplementary Table 3 ). Heatmap showed the significantly downregulation of TGFB1 32 , ETV1 33 , CSF1 34 , BMP7 35 , SGMS2 36 , CXCL14 37 and S100A4 38 which have been reported to enhance protumor macrophage polarization via various pathways. (Figure 4 E).…”
Section: Resultsmentioning
confidence: 99%
“…Inhibiting the enzyme with YE2 reduces CSF1R levels and controls macrophage differentiation into the M2 phenotype. Deletions of sphingomyelin synthase 2 or utilization of YE2 can inhibit tumor progression by weakening the invasion and function of TAMs, which may be a promising-targeted treatment scheme ( 177 ).…”
Section: Immunosuppressive Molecules and Targeted Therapymentioning
confidence: 99%
“…MARCO reduces the infiltration of CD8 + T cells and NK cells in PDAC and inhibits effective anti-tumor immunity. The utilization of MARCO-targeted antibodies induces the repolarization of TAMs, improves the level of IL-18, and strengthens the function of anti-tumor cells (176).…”
Section: Immunosuppressive Molecules and Targeted Therapymentioning
confidence: 99%
“…4B and supplementary Table 3). Heatmap showed the signi cantly downregulation of CCL22 [32], TGFB1 [33], ETV1 [34], CSF1 [35], BMP7 [36], SGMS2 [37], CXCL14 [38] and S100A4 [39] which have been reported to enhance protumor macrophage polarization via various pathways. (Fig.…”
Section: Mnda Enhances M2 Macrophages Polarizationmentioning
confidence: 99%